(3GdeNJGQ ef eOjM GdeNJGQs - (3eLghds; (3jMji Hf jhSa Hf jMji GdCfUGQj, GdUQUQj, LeGd GdOjf CHh RcQjG,J (B656 (3g` s ((3Ydj Hf YeQ Hf Ydj GdTGaYj s)
(3ChdgG (B:s
(3bGd GdTjN LeGd GdOjf jeOM SjOfG eMeOkG Udi Gddg Ydjg hSde Ydi bGajI GdgeRI(B: (3SHMGf ef ddhQi aj CQVg nOQB hCMSf GdUfY HGdEJbGf EPHQB s
(3BNQgG (B:s
(3hdG RGdJ dc GdCfhGQ oJgOi haj GdoCNQi dc GdRdai oJgjG Je GdeNJGQ ef eOM QShd Gddg Udi Gddg Ydjg hSde ddEeGe LeGd GdOjf hMSHfG Gddg s
(3GdfSNI HgG MhGTs
(3eQJHI Ydi GdbhGajs
(3fSNI NRGFfjI fajSI cJHJ dNRGfI Gdehdi HOQGdOjf GdESYQOjs
(3HgGeTgG HYV GdeYGfj HNW GdfSN faSg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdCOHs